Policy innovations for transformative change implementing the 2030 Agenda for Sustainable Development (UNRISD flagship report, 2016)
This UNRISD Flagship Report helps unpack the complexities of the 2030 Sustainable Development Agenda by focusing on policy change, and analysing which policies and practices will lead to social, economic and ecological justice. Drawing on policy innovations, the report brings a definition of transformation which can be used for policy making toward the 2030 Agenda. Bringing together five years of UNRISD research across six areas—social policy, care policy, social and solidarity economy, eco-social policy, domestic resource mobilization, and politics and governance—the report explores what transformative change really means for societies and individuals